Mapping Maqāṣid Sharia Models in Islamic Economics: A Scoping Review of Literature (2018-2022) - Muttaqin, Aris Anwaril; Samsudin, Muhammad Adib; Salleh, Ahmad Dahlan; Ahmad, Azlin Alisa; Hawa, Nabila Nurul (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2025)
Maqāṣid Sharia is a foundational epistemological framework for developing Islamic economics. Despite increasing scholarly attention, prior studies have inadequately mapped the diversity of Maqāṣid Sharia models employed in the discipline. This study aims to address that gap through a scoping literature review of publications from 2018 to 2022 indexed in Scopus and Web of Science, identifying the primary models applied by researchers. The analysis reveals four dominant conceptualizations: maṣlaḥah and mafsadah, kulliyāt al-khams, contemporary maqāṣid, and ḥifẓ al-māl. While the overarching term